HSP70 and HSP90 in Cancer: Cytosolic, Endoplasmic Reticulum and Mitochondrial Chaperones of Tumorigenesis - Albakova, Zarema; Mangasarova, Yana; Albakov, Akhmet; Gorenkova, Liliya (Frontiers in Oncology, 2022)
HSP70 and HSP90 are two powerful chaperone machineries involved in survival and proliferation of tumor cells. Residing in various cellular compartments, HSP70 and HSP90 perform specific functions. Concurrently, HSP70 and HSP90 homologs may also translocate from their primary site under various stress conditions. Herein, we address the current literature on the role of HSP70 and HSP90 chaperone networks in cancer. The goal is to provide a comprehensive review on the functions of cytosolic, mitochondrial and endoplasmic reticulum HSP70 and HSP90 homologs in cancer. Given that high expression of HSP70 and HSP90 enhances tumor development and associates with tumor aggressiveness, further understanding of HSP70 and HSP90 chaperone networks may provide clues for the discoveries of novel anti-cancer therapies.